Deciphering the Cenozoic Exhumation History of the Eastern Pyrenees Along a Crustal‐Scale Normal Fault Using Low‐Temperature Thermochronology. Issue 4 (16th April 2022) - Milesi, G.; Monié, P.; Soliva, R.; Münch, P.; Valla, P. G.; Brichau, S.; Bonno, M.; Martin, C.; Bellanger, M.
Abstract: The timing of transition between the contractional and extensional regimes along the Pyrenean range remains debated. Compared to its central and western parts, the eastern part of the chain was significantly affected by extensional tectonics mostly related to the opening of the Gulf of Lion. The Têt normal fault is the best example of this tectonic activity, with topographic reliefs above 2, 000 m in its footwall. In this study, we synthetized previous thermochronological data and performed new (U‐Th)/He and fission track dating in the Eastern Pyrenean massifs. Output apparent exhumation rate and thermal modeling in the hanging wall of the Têt fault highlight a rapid exhumation (0.48 km/Ma) and cooling (∼30°C/Ma) phase between 38 and 35 Ma, followed by slower exhumation/cooling afterward. In the footwall, cooling subsequently propagated westward along the fault during Priabonian (35–32 Ma), upper Oligocene and lower Miocene (26–19 Ma), and Serravallian‐Tortonian times (12–9 Ma). These data and modeling outcomes suggest that the exhumation of the Têt fault hanging wall related to southward thrusting ended at 35 Ma, and was followed by different extensional stages, with a propagation of the deformation toward the West during the upper Miocene. We propose that the onset of extension in the Eastern Pyrenees occurred during the late Priabonian period, contemporaneously with the large‐scale rifting episode recorded in Western Europe. After this event, the Têt fault activity and the westward propagation of the deformation appear mainly controlled by the opening of the Gulf of Lion. Plain Language Summary: The Pyrenees result from the North‐South convergence of the Eurasian and Iberian plates. The eastern part of the range experienced strong extensional tectonics mostly related to the opening of the Gulf of Lion, which timing and influence on the modern topographic relief remain unclear. To better characterize the transition timing between contractional and extensional regimes and the tectonic evolution in the Eastern Pyrenees, we used low‐temperature thermochronology and thermal modeling to reconstruct the exhumation/cooling histories of the different massifs along the Têt fault. Our data and modeling outcomes show a switch between contractional and extensional tectonics during the Priabonian (ca. 35 Ma), followed by different extensional stages recorded in the Têt fault footwall, coeval with a global westward propagation of the deformation along the fault until ca. 9 Ma. Key Points: Tectonic evolution along a major normal fault recorded by low‐temperature thermochronology Priabonian (35–32 Ma) switch between contractional and extensional regime in the Eastern Pyrenees Cenozoic westward propagation of the deformation along the Têt fault